Involuntary movements associated with correction of vitamin B12 deficiency?: A case report - Bendezú-Barnuevo, Daniela (2021)
Background: Vitamin B12 deficiency is a nutritional problem that can present with neurological and hematological manifestations. There are limited reports on the appearance of involuntary movements when initiating cyanocobalamin treatment. Case report: A 5-month-old infant presented vomiting, paleness, and difficulty holding his head. Among the examinations, pancytopenia and vitamin B12 deficiency were found in the patient and the mother. Treatment with folic acid and cyanocobalamin was administered; However, on the fourth day of treatment, she presented choreiform movements for which clonazepam was administered. The tomography and the electroencephalogram were normal. At follow-up, the platelet and leukocyte count improved and the movements gradually remitted. Conclusion: Little is reported about the occurrence of involuntary movements when vitamin B12 deficiency is corrected. Follow-up evaluation is important to avoid unnecessary overmedication.